2013
DOI: 10.1021/jm301708u
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2-(Phenoxypyridine)-3-phenylureas as Small Molecule P2Y1 Antagonists

Abstract: Two distinct G protein-coupled purinergic receptors, P2Y1 and P2Y12, mediate ADP-driven platelet activation. The clinical effectiveness of P2Y12 blockade is well established. Recent preclinical data suggest that P2Y1 and P2Y12 inhibition provide equivalent antithrombotic efficacy, while targeting P2Y1 has the potential for reduced bleeding liability. In this account, the discovery of a 2-(phenoxypyridine)-3-phenylurea chemotype that inhibited ADP-mediated platelet aggregation in human blood samples is describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 34 publications
3
44
0
Order By: Relevance
“…However, it should be noted that only very few allosteric antagonists have been used in crystallization compared with the total population of GPCR antagonists available. Even for the urea class of P2Y 1 R antagonists related to BPTU, the binding location was initially predicated by molecular modeling to be within the helical bundle (Chao et al, 2013;Qiao et al, 2013). Thus, potentially biased functional antagonism remains to be explored for other P2Y 1 R antagonists and for diverse antagonists, especially allosteric modulators, of other GPCRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that only very few allosteric antagonists have been used in crystallization compared with the total population of GPCR antagonists available. Even for the urea class of P2Y 1 R antagonists related to BPTU, the binding location was initially predicated by molecular modeling to be within the helical bundle (Chao et al, 2013;Qiao et al, 2013). Thus, potentially biased functional antagonism remains to be explored for other P2Y 1 R antagonists and for diverse antagonists, especially allosteric modulators, of other GPCRs.…”
Section: Discussionmentioning
confidence: 99%
“…1) bound in a pocket formed within the seven transmembrane (TM) domains and more external than most small ligands of rhodopsin-like GPCRs. However, an allosteric antagonist 1-(2-(2-(tert-butyl)phenoxy)-pyridin-3-yl)-3-(4-(trifluoromethoxy)phenyl)urea (BPTU), a hydrophobic diaryl-urea derivative that arose from a program to develop antithrombotic drugs (Chao et al, 2013), bound on the external receptor surface at the phospholipid membrane interface in contact with TMs 1-3 (Zhang et al, 2015a). This represented the first example in the GPCR field of a ligand located outside the helical bundle or loop regions.…”
Section: Introductionmentioning
confidence: 99%
“…Semitransparent surface of binding site's residues is displayed in pale cyan. (Chao et al, 2013) were recently determined (Fig. 4B) (Zhang et al, 2015).…”
Section: Structural Characterization Of P2yrsmentioning
confidence: 94%
“…In their discovery program a high throughput screening (HTS) effort, using >1 million compounds against the human P2Y1R, revealed that diarylurea 8 30 had good affinity and binding selectivity toward the P2Y1R versus P2Y12R (P2Y1 Ki = 75 nM, P2Y12 Ki > 70 μM).…”
mentioning
confidence: 99%